Russia's Turn to the East Domestic Policymaking and Regional Cooperation - Blakkisrud, Helge; Wilson Rowe, Elana (Global Reordering, 2018)
Development studies; Russia; Far East; International affairs; Energy; Shanghai cooperation organization; Economic development; Security policy; Multilateral organizations; Diplomacy; Regionalism; Russian-European relations; Russia's "pivot to the East"; Annexation of Crimea; Regional politics; Eurasia; Ukraine; Sanctions regime; Foreign policy